ISTORIOGRAFIA DESPRE CULTURA ROMÂNEASCĂ ÎN BASARABIA ÎN SEC. AL XIX-LEA. ŞTEFAN CIOBANU - MIHAIL, Zamfira (BIBLIOPOLIS, 2020)
The author presents an aspect poorly studied in our country: the history of Romanian culture in Bessarabia under the rules of Russian Empire (19th century - beginning the 20th). As a model approach of this subject is analysed the work of the historian Stefan Ciobanu (1883-1950), the first Bessarabian, member of the Romanian Academy. The prof. Stefan Ciobanu wrote a monography and several studies about the Romanian culture in Bessarabia of this period. In the works is highlighted the conservation of essential spiritual values: Romanian language, ortodox faith, folklore, traditions, habits etc.